2017
DOI: 10.1101/cshperspect.a031849
|View full text |Cite
|
Sign up to set email alerts
|

Kras and Tumor Immunity: Friend or Foe?

Abstract: With the recent breakthroughs in immunotherapy as curative treatments in certain tumor types, there has been renewed interest in the relationship between immunity and tumor growth. Although we are gaining a greater understanding of the complex interplay of immune modulating components in the tumor microenvironment, the specific role that tumor cells play in shaping the immune milieu is still not well characterized. In this review, we focus on how mutant Kras tumor cells contribute to tumor immunity, with a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 155 publications
2
81
0
Order By: Relevance
“…End stage tumors with genetic alterations in Kras exhibited marked modulation of the immune response, including reduced expression of inflammatory cytokines and increased markers of activated myeloid cells. These findings are consistent with the literature describing immune evasion by Kras activation by multiple mechanisms, including reduced expression of tumor antigens, and promotion of recruitment and differentiation of immune populations that inhibit anti-tumor immune activity (Cullis et al, 2017;Dias Carvalho et al, 2018) . Future studies will elucidate interactions between preneoplastic/malignant epithelial cells and the immune microenvironment through stages of PRL-induced pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…End stage tumors with genetic alterations in Kras exhibited marked modulation of the immune response, including reduced expression of inflammatory cytokines and increased markers of activated myeloid cells. These findings are consistent with the literature describing immune evasion by Kras activation by multiple mechanisms, including reduced expression of tumor antigens, and promotion of recruitment and differentiation of immune populations that inhibit anti-tumor immune activity (Cullis et al, 2017;Dias Carvalho et al, 2018) . Future studies will elucidate interactions between preneoplastic/malignant epithelial cells and the immune microenvironment through stages of PRL-induced pathogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Ren et al reported that TGF‐β could promote the migration of PC cells by inducing EMT during the activation of WNT signalling pathway 48 . The activation of TGF‐β signalling pathway promotes Treg cells recruitment and TAMs polarization and induces immunosuppression in the TME 49,50 . Additionally, existing studies suggests a critical positive feedback loop between the activation of EMT and the infiltration of TAMs in cancers, which, in turn, induce immune evasion and suppression in the TME 51‐53 .…”
Section: Discussionmentioning
confidence: 99%
“…Several chemokines have been implicated in inflammation-induced tumorigenesis 39 . Chemokine C-C motif ligand 5 (CCL5), also known as Regulated upon Activation, Normal T-cell Expressed and Secreted (RANTES), mediates migration and chemotaxis of cells and is expressed by several cell types such as fibroblasts, epithelial cells, tumour cells and immune cells.…”
Section: Kras-induced Inflammationmentioning
confidence: 99%